The performance of the higher-order radiation condition method for the penetrable cylinder - YILMAZ, BÜLENT (HINDAWI LTD, 2007)
We have considered the scattering of a plane wave by a penetrable acoustic circular cylinder. The boundary conditions are continuity of the total pressure and the total velocity. The wave speed and density of the target are different from that of the surrounding medium. We investigated the performance of higher-order SRCs up to L-4 operator in two dimensions. We assume that in the rectangular Cartesian system of axes, (x, y, z), the z axis coincides with the axis of the cylinder and an incident wave propagates in a direction perpendicular to the z axis. All the field quantities are then independent of z. Numerical results are added to present the change of the module of the total field and the magnitude of the far field with respect to theta. Copyright (c) 2007 Bulent Yilmaz.
Keywords: SCATTERING